The structure of German - Fox, Anthony, 1943- (Oxford linguistics., 2005)
The new edition of The Structure of German has been fully revised to take account of developments in the subject. The author describes German phonology, morphology, syntax, semantics, and pragmatics. He introduces linguistic theory in order to throw light on every aspect of the language, providing students with a linguistically informed and accessible approach to the description of the language. Updated guides to further reading are given at the end of each chapter, and the. book's usefulness for students and teachers has been enhanced by the addition of exercises and discussion questions. Thi.